The development study of Leuwimunding Religious Tourist Village in Majalengka - Fasya, Muhammad Najih; Putra, Muhammad Rifqi Ananda (School of Tourism, Universitas Ciputra Surabaya, 2025)
This article investigates the potential of Leuwimunding Village, Majalengka Regency, West Java, to be developed as a religious tourism village, with the research objective of assessing the feasibility of Leuwimunding Village as a religious tourism destination. The village holds significant religious importance due to the presence of the grave of national hero KH. Abdul Chalim, a revered figure in Indonesian Islam. Despite this, Leuwimunding's potential for religious tourism has not been fully realized, highlighting the need for a strategic development approach. The article employs a multi-approach methodology, combining a comprehensive rational approach with realist and critical ethnography. This methodology allows for an in-depth understanding of the village's socio-cultural context, the historical significance of KH. Abdul Chalim, and the potential for religious tourism development. Additionally, the article incorporates a participatory approach, engaging with local communities and stakeholders to ensure their involvement in the development process. The findings reveal that Leuwimunding Village possesses strong potential for religious tourism, driven by the historical and spiritual significance of KH. Abdul Chalim's legacy. The article identifies specific aspects of the village's cultural and religious identity, including its connection to the Nahdlatul Ulama (NU) movement and its unique Sundanese cultural heritage. These elements enhance the village's attractiveness for religious tourists seeking authentic and meaningful experiences. The article concludes with recommendations for the sustainable development of Leuwimunding as a religious tourism village, emphasizing the importance of preserving the village's cultural and religious heritage, promoting community involvement, and developing infrastructure and services that cater to the needs of religious tourists.